Islam in the Crimea in the 14th–18th centuries » - I.V. Zaytsev (Золотоордынское обозрение)
Prior to 1783, the historical development of Islam in Crimea is divided into at least two stages. The first stage is connected with the influence of the eastern lands of the Golden Horde, which included the Crimean ulus, as well as of the Mamluk Egypt. The second phase began in 1475 when, after the Ottoman conquest of the southern coast of the peninsula, the Crimean Khanate experienced strong cultural and religious influence of the Ottomans. However, the weakened Central Asian influence did not disappear completely, since the Ottoman Crimea was on the way of the Central Asian pilgrims. Beginning in the late 15th century, we see representatives of the ulama, Seyyids and revered sheikhs at the top of the hierarchy, among immediate circle of khans. The process of Islamization of the Khan’s court and the Office on the Ottoman style apparently was largely completed by the reign of Sahib Giray, who appears in the description of his panegyrist as a highly devout ruler. At the same time, the Crimean Islam gave birth to such a specific local phenomenon as worship of the Azizes – the graves of revered personages of the worldwide and local Islamic History.